Implementation Of The Utilization Of Zakat Mal Funds In The Education Sector (Study Of The Jabar Cerdas Education Program Of BAZNAS West JavaProvince) - Ridha Hisna Nadiyya (Journal of Islamic Economics and Philanthropy, 2022)
BAZNAS as a philanthropic institution in charge of collecting and managing zakat funds contributes to the state to be able to improve the quality of human resources (Human Resources) to achieve development targets, one of which is through planning JABAR CERDAS education programs as a utilization step to maximize the zakat mal funds that have been collected. The purpose of this study is to find out the utilization and optimization of appropriate and targeted zakat mal funds in the JABAR CERDAS Education Program of BAZNAS West Java Province. In the preparation of this thesis, the author uses a descriptive qualitative approach. The data sources used are primary data and secondary data. Research data collection techniques are carried out by observation, interviews, and documentation. The data analysis, techniques used in this study are qualitative inductive with data reduction, data presentation, and the last step is the withdrawal of conclusions. The result of this study is the utilization of zakat mal funds in the JABAR CERDAS Education Program of West Java Province, which is overall creative consumption. But in addition, the programs implemented are conventional productive in which scholarship recipients are given opportunities in the form of mentoring activities as a form of human empowerment efforts that are expected to change those who were original as mustahik, it will become muzakki. The utilization stage is included in the distribution of utilization. For the utilization pattern, it can be seen that the utilization pattern implemented by BAZNAS West Java Province is a contemporary (productive) pattern.Keywords: Utilization, Zakat Mal, Education